1949
DOI: 10.1021/ja01177a531
|View full text |Cite
|
Sign up to set email alerts
|

The Bio-Oxygenation of 11-Desoxycorticosterone at C-11

Abstract: Communications to the Editor 3261 Preliminary fractionation of the benzene-extractable alkaloids by the excellent procedure of Jacobs and Craig4 yielded the five known crystalline alkaloids and a large amorphous fraction; only the latter was active as a hypotensive agent at low dosage. Further fractionation of this material guided by assay3 in hypertensive patients yielded a highly active concentrate, which on 24-plate Craig distribution, using 2 M acetate buffer at pH 5.5 and benzene as the immiscible phases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1950
1950
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Cytochrome P-450's can catalyze the insertion of oxygen between a C atom and a hydrogen atom [1]. Insertion of • OOH into a C atom bearing a tertiary H atom (e.g.…”
Section: Sidechain Cleavagementioning
confidence: 99%
“…Cytochrome P-450's can catalyze the insertion of oxygen between a C atom and a hydrogen atom [1]. Insertion of • OOH into a C atom bearing a tertiary H atom (e.g.…”
Section: Sidechain Cleavagementioning
confidence: 99%
“….perfusion of the isolated beef gland with 11-desoxycorticos terone led to the production of corticosterone (113). This ability of the gland to effect l1-oxygenation is not confined to ll-desoxycorticosterone since 11-hydroxyandrosterone has been isolated after perfusion with androsterone and 17 -hydroxycorticosterone after perfusion with 17a-hydroxy-ll-desoxy corticosterone; l1-oxygenation of other steroids (e.g., progesterone, 17a hydroxyprogesterone) is indicated (114). Since this l1-oxygenation is effected in the absence of ACTH, and is not materially enhanced by the addition of ACTH to the perfusate, this step in the biosynthesis of typical adrenocor ticosteroid is obviously beyond ACTH control.…”
Section: Adrenal Cortex Hormonesmentioning
confidence: 99%
“…Employing a perfusion apparatus recently described (111), Hechter has ob served the increased production of formaldehydogenic neutral lipid and con comitant glycogenic activity after the addition of ACTH to the perfusion medium (112) . .perfusion of the isolated beef gland with 11-desoxycorticos terone led to the production of corticosterone (113). This ability of the gland to effect l1-oxygenation is not confined to ll-desoxycorticosterone since 11-hydroxyandrosterone has been isolated after perfusion with androsterone and 17 -hydroxycorticosterone after perfusion with 17a-hydroxy-ll-desoxy corticosterone; l1-oxygenation of other steroids (e.g., progesterone, 17a hydroxyprogesterone) is indicated (114).…”
Section: Adrenal Cortex Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful experiments reported by a number of workers [Hechter, Jacobsen, Jeanloz, Levy, Marshall, Pincus & Schenker, 1949, 1950Hayano, Dorfman & Prins, 1949;Nissim, 1952], demonstrating the ability of the adrenals to convert mineralocorticoids into gluco-corticoids, suggested that similar enzymic transformations of steroids might take place in other endocrine organs. Therefore, an investigation of the capacity of the corpus luteum to synthesize progesterone from other steroids was undertaken.…”
mentioning
confidence: 99%